2013
DOI: 10.1128/jcm.01935-13
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of BacT/Alert FA Plus and FN Plus Bottles Compared with Standard Bottles

Abstract: The performance of the BacT/Alert FA Plus and FN Plus resin bottles was evaluated in comparison with that of standard aerobic (SA) and standard anaerobic (SN) bottles. Twenty milliliters of blood from adult patients was equally distributed into four types of bottles: FA Plus, FN Plus, SA, and SN. The detection of clinically significant organisms and the time to detection (TTD) were monitored for each bottle. Among the 3,103 blood culture sets that were requested, the blood volume of each bottle was over 4 ml i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 16 publications
1
31
1
1
Order By: Relevance
“…The BacT/Alert Plus system detected clinically relevant BSIs after a mean incubation of 16 h (IQR, 9 to 21 h), and for certain species, TTDs were frequently Ͻ12 h, which is consistent with previous reports (40)(41)(42). The TTDs for positive BacT/Alert and Bactec cultures drawn after antimicrobial drugs had been started were comparable, but the former system was faster for treatment-negative samples and those containing coagulase-negative staphylococci.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The BacT/Alert Plus system detected clinically relevant BSIs after a mean incubation of 16 h (IQR, 9 to 21 h), and for certain species, TTDs were frequently Ͻ12 h, which is consistent with previous reports (40)(41)(42). The TTDs for positive BacT/Alert and Bactec cultures drawn after antimicrobial drugs had been started were comparable, but the former system was faster for treatment-negative samples and those containing coagulase-negative staphylococci.…”
Section: Discussionsupporting
confidence: 78%
“…Three recent studies (40)(41)(42) have demonstrated the superiority of the new resin-containing BacT/Alert media (FA Plus, FN Plus, and PF Plus) over standard and charcoal particle-containing media of the same line. In our study, the performance displayed by BacT/Alert Plus media was similar to that of resin-containing media in the Bactec line.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current standard blood culture procedures consist of inoculating a blood culture bottle and placing it on an automated continuous monitoring and alert platform (8). Upon positivity, the contents are Gram stained, plated on appropriate media, and allowed to grow for 18 to 42 hours or longer, with subsequent subcultures and susceptibility testing as appropriate.…”
mentioning
confidence: 99%